DYNAMICS OF LAND LAW: AN ANALYSIS OF THE NEED FOR LEGAL REFORM IN INDONESIA - Gloria Gita Putri Ginting; Ayu Kurnia Sari (RADJA PUBLIKA, 2023)
Land law in Indonesia faces complex challenges due to ownership conflicts, overlapping regulations, and weak law enforcement. The mismatch between outdated regulations and the needs of modern society often gives rise to land disputes, uncertainty over rights, and obstacles to investment. This study analyzes the dynamics of land law in Indonesia, focusing on the urgency of legal reform. The methods used are normative studies and descriptive analysis of laws and regulations, court decisions, and related literature. The findings indicate that land law reform is needed to harmonize regulations scattered across various laws, strengthen legal certainty, and increase public access to land rights. Furthermore, improving administrative procedures, simplifying certification mechanisms, and protecting the rights of indigenous peoples are crucial aspects of reform. This study emphasizes the need for regulatory harmonization and increasing the capacity of law enforcement agencies to reduce land conflicts. In conclusion, land law reform is not only crucial for social and economic stability but also serves as a foundation for equitable, sustainable development. With effective reform, it is hoped that land rights security for all levels of society can be achieved, disputes can be minimized, and a healthy investment climate can be supported.